Investigation of even-even (〖Ra〗^(220-224))(〖Rn〗^(220-224))(〖Th〗^(220-224)) isobars within the IBM-2 and IVBM - Dalenda M. Nasef; Mariam I. Al-twairy; Asma A. Elbendag (African Journal of Advanced Pure and Applied Sciences, 2025)
In this study, we determined the most appropriate limit using the IBM-2 model and the IVBM model that is needed for present calculations of isobars . To determine the characteristics of each isotope inside the aforementioned isobars, we computed energy levels ‎and compared the outcomes with the experimental data, and then the values of the ratio , the E-GOS curve, and the ratio were adopted. From these values it was possible to determine the dynamic symmetries of each isotope, since ( were classified as having O(6) symmetry, while the isobars ( have X(5) symmetry, the isobars ( ) and ( ) have E(5) symmetry, and the has U(5) symmetry. The phenomenon of back bending of these isobars, which was all unbinding, was studied.